The ADEBAR project: European and international provision of analytical data from structure elucidation and analytical characterization of NPS. Issue 8 (24th May 2022) - Pulver, Benedikt; Fischmann, Svenja; Westphal, Folker; Schönberger, Torsten; Schäper, Jan; Budach, Dennis; Jacobsen‐Bauer, Andrea; Dreiseitel, Wolfgang; Zagermann, Johannes; Damm, Angela; Knecht, Siegfried; Opatz, Till; et al.
Abstract: Novel substances for which none or limited analytical data are available constitute a challenge for police and customs forensic laboratories. The time‐consuming process of structural elucidation and acquisition of analytical data has been centralized in the ADEBAR project in Germany, co‐funded since 2017 by the EU's Internal Security Fund. The project aims to comprehensively characterize substances relevant for forensic‐toxicological casework within the analytical competence network. The analytical datasets are distributed digitally through European and (inter)national channels. Additionally, pharmacological evaluation allows for estimating in vivo potency and potential harm required as scientific evidence for legislative amendments. The ADEBAR project contributes to the availability of analytical data on new substances relevant to the daily work of police and customs laboratories. Since the inception of the ADEBAR project, 549 samples have been registered, and 302 substance reports notified to the EMCDDA, including numerous spectrometric and spectroscopic data. In addition, 3, 619 mass spectra have been accumulated in ADEBAR mass spectra databases. A central institution for the structure elucidation and acquisition of valid, high‐quality analytical data for police and customs forensic laboratories and forensic medicine institutes is important in the future because there does not seem to be an end to the dynamic of novel NPS appearing on the drug market. Abstract : EU‐funded ADEBAR project for the analytical characterization of NPS and substances emerging on the drug market relevant to the forensic community.